Asclepius Amidst the Flames of War: Medical Relief at Canton Hospital During the War of Resistance - CUI Junfeng, (Journal of Research for Christianity in China (JRCC), 2025)
The War of Resistance Against Japan from 1937 to 1945 was the first nationwide struggle against foreign aggression in modern Chinese history. During this conflict, numerous Westerners and institutions originally established by foreigners in China—such as the Guangzhou Canton Hospital—participated, making significant contributions to the victory. Throughout the war, the Guangzhou Canton Hospital Hospital organized the Guangzhou International Red Cross Service Corps to deploy to the front lines for battlefield medical rescue operations. The hospital endured repeated relocations and struggled to survive, while also establishing the Lingnan University Refugee Camp to aid displaced persons and provide medical services to nearby villages. Its efforts in treating war casualties perfectly embodied the compassionate spirit of Asclepius, the god of medicine, who saved lives through healing amidst the ravages of war. Revealing Guangzhou Canton Hospital Hospital's experiences and contributions during the War of Resistance not only enriches our historical understanding but also allows us to examine the bonds of friendship forged in blood and fire among the peoples of the world during the anti-fascist war against aggression.